The Monastery near Kıyıköy in European Turkey - Portalsky, Alexandar; Bagasheva, Mariya (Studia Ceranea, 2023)
The monastery near today’s Kıyıköy settlement on the Black Sea coast is a very interesting rock-cut complex. It probably inherited an ancient sanctuary near the ancient Thracian and Roman city of Salmydessos, which became an important Christian center in the vicinity of Constantinople. In this text, we briefly review the historical information about the city, then describe the monastery, because there has been only one scientific publication since 1970 and the monastery is very difficult to access. We apply the three plans of the monastery that have been published since the 19th century to trace the change in the condition of the rock and the rooms that have been added. Then we analyze the architectural program and types of decoration of the three-nave basilica and the sacred spring, which have no exact analogue and are comparable both to examples from antiquity and to the best temples in the Byzantine capital. Based on this analysis, we assume three construction periods – ancient, from the time of Justinian and from the end of the iconoclastic period after the destruction of the city by the Bulgarian Khan Krum.